Hubungan Terpaan Isu Produk Palsu Scarlett Whitening Dan Terpaan Media Sosial Instagram Scarlett Whitening Dengan Sikap Konsumen Dalam Menggunakan Produk Scarlett Whitening - Radinda N Harahap; Joyo Nur Suryanto Gono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The attitude of consumers in using or consuming a product is formed from various factors that exist within them, for example, the strong experience that a person has and social media. In this regard, the Scarlett Whitening brand has problems with the issue of counterfeit products circulating in Lazada e-commerce and is feared to have an impact on consumer attitudes themselves. But the good news is that the Scarlett Whitening brand itself provides a solution to this problem by providing a barcode that can be checked on the official Scarlett Whitening website. This strategy is also promoted by the Scarlett Whitening brand through their Instagram social media. This study aims to determine the relationship between exposure to the issue of Scarlett Whitening's counterfeit products and exposure to Scarlett Whitening's Instagram social media with consumer attitudes in using Scarlett Whitening products, using the Cognitive Response Theory and Individual Difference Theory. Based on the results of this study using Kendall's Tau-b analysis and having a sample of 50 respondents, it is known that there is no connection between each of the variables studied. The variable exposure to the issue of Scarlett Whitening counterfeit products and consumer attitudes in using Scarlett Whitening products has a value of 0.063 ≥ 0.05 and is proven to be insignificant. Likewise for the Scarlett Whitening Instagram social media exposure variable with consumer attitudes in using Scarlett Whitening products, it has a significance value of 0.116 ≥ 0.05. Therefore, for future researchers who will conduct research with similar variables, it is advisable to look for other variables related to consumer attitudes such as word of mouth, brand image, level of trust, and perceived risk.